(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Due to the increasing market penetration in developing countries e-waste becomes the one of the fastest growing waste streams. The presences of toxic and hazardous substances in electronic goods have adverse affects on environment. Here in this paper I offer an overview of threat of e-waste on woman health and environment including its management and disposal option. Management of e-waste mainly depends on four steps that are reduced, reused, recycle and last option is disposed. Preventing waste in the first place is the preferred management option which can be achieved to repairing and upgrading the equipment. Through recycling either reused or dismantled for recycling the silver, gold, lead and another heavy metal are recyclable. In India entire recycling occurs by unauthorized and unorganized sector where the process done in such a manner which cause to exploitation of woman health and also to environment. The least preferred option is to landfill e-waste. That’s why it is important to create a national frame work in making rules for e-waste for the environmentally sound management of e-waste including wide public awareness and education.